Environmental impact assessment of earthquake-generated construction and demolition waste management: a life cycle perspective in Turkey - Bilgili, Levent; Cetinkaya, Afsin Yusuf (SPRINGERNATURE, 2024)
Construction and demolition waste consists of residue and discarded materials that result from construction, renovation, remodelling, and demolition activities. This waste typically includes various materials, such as concrete, wood, steel, bricks, drywall, asphalt, glass, plastics, and other construction-related materials. This research quantified the environmental consequences of managing earthquake-generated construction and demolition waste in Turkey using diverse techniques. The study employed a life cycle assessment to compute these impacts. First, the impacts of the currently used landfill process were calculated and then a scenario in which concrete is reused, recyclable wastes are separated and recycled, and the remaining waste is sent to a landfill was created. According to the findings, it is seen that if all the debris is sent to a landfill, 11.9 t CO(2)eq will be generated in the short term, while 18,428.3 t CO(2)eq can be saved, especially by reusing concrete. These findings may vary due to the involvement of different unforeseen processes, but they show that although it is often very difficult to utilize such wastes, especially those generated as a result of unusual disasters, such as earthquakes, very significant environmental gains can be achieved through appropriate treatment.
Keywords: Construction and demolition waste; Life cycle assessment; Earthquake debris; ASSESSMENT LCA; CONCRETE; Environmental Sciences & Ecology; Operations Research & Management Science